2011
DOI: 10.1021/jp202241m
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the In-Solution Isomeric Protonation of Non-Aromatic Six-Member Rings with Two Nitrogens

Abstract: For exploring the preferred site for hydrogen bond formation, theoretical calculations have been performed for a number of six-member, non-aromatic rings allowing for alternative protonation on the ring nitrogens. Gas-phase protonation studies for test molecules indicate that the B3LYP/aug-cc-pvtz and QCISD(T)CBS calculations approach the experimental values within about 1 kcal/mol with considerable improvement for relative enthalpies and free energies. Relative free energies calculated at the IEF-PCM/B3LYP/au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Accurate theoretical prediction of the free energy of hydration for a molecule is, however, challenging. The gas-phase term could be reliably predicted; the protonation energy and gasphase basicity were successfully calculated recently for a few molecules [41,42] applying satisfactorily high-level of energy calculations and by assuming ideal gas behavior. By combination of the classical limit expression for the translational, rotational energy and entropy and using the rigid-rotor/harmonic oscillator approach, [43] good agreement with experimental values was reached.…”
Section: Continuum Solvent Modelsmentioning
confidence: 94%
See 2 more Smart Citations
“…Accurate theoretical prediction of the free energy of hydration for a molecule is, however, challenging. The gas-phase term could be reliably predicted; the protonation energy and gasphase basicity were successfully calculated recently for a few molecules [41,42] applying satisfactorily high-level of energy calculations and by assuming ideal gas behavior. By combination of the classical limit expression for the translational, rotational energy and entropy and using the rigid-rotor/harmonic oscillator approach, [43] good agreement with experimental values was reached.…”
Section: Continuum Solvent Modelsmentioning
confidence: 94%
“…The counterion effect becomes nearly negligible only at about R = 12 Å. Recent studies suggest, however, that a free chloride counterion would wander in the solution and takes sometimes a hydrogen bond with the cation, whereas the cation -anion distance may increase temporarily even to about 14 Å in a dilute solution [37,41,42,112].…”
Section: Other Equilibriamentioning
confidence: 98%
See 1 more Smart Citation
“…For details of the methodology applied, see also recent papers. [25][26][27] Using the BOSS 4.8 package, 28 the all-atom OPLS-AA 12-6-1 pair-potential 29,30 was applied, and the 12-6 Lennard-Jones parameters were taken from the program's library. The atomic charges were fitted to the IEF-PCM/B97D/aug-cc-pvtz molecular electrostatic potential, generated on the basis of the solute's electron distribution polarized by the solvent, by means of the CHELPG procedure.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…Previous studies indicated, however, that the ion and the counterion stay generally close to each other in a slightly polar solvent, and maintain a fairly stable hydrogen-bonded ion-pair. 26,39 Thus a bonded Cl À Á Á Á + H 3 NCH 2 CH 2 NH 2 model was optimized in chloroform. This is the other extreme structure for an ion-pair compared with the fully dissolved and separated model.…”
Section: Relative Energies/free Energiesmentioning
confidence: 99%